A instrumentalidade do processo trabalhista com o emprego dos recursos tecnológicos - Ferreira, Maria Lúcia de Freitas Petrucci (2008)
Society digs solutions for its conflicts in a fast and effective way, and the same happens in labor disputes. Several attempts were employed, however, they have not reached society pacification yet, since many times other conflict points are generated, taking in consideration that the existing mechanisms are ineffective and obsolete to solve them Unexpectedly, technological resources have appeared at the labor ambit, therefore achieving fast and effective judicial proceedings. Information technology aid at Labor Law, in other words the electronic proceedings, are still being improved; nevertheless it intends to reach the apex, which would be the virtual justice proceeding, since they are tracks to be followed with new clothes, aiming at satisfactory results for social pacification. This experience can be confirmed by analyzing a field research performed at State Justice Virtual Forum in Freguesia do Ó, neighborhood in the city of São Paulo, where the labor proceedings are actually instrumental with beneficial reflexes to society